Pulmonary metastasis of hepatocellular carcinoma: pathogenesis and therapeutic advances - GUAN Tao, ZHANG Ti, WANG Lu (Waike lilun yu shijian, 2022)
In recent years, the survival of patients increased with development of treatment modalities for hepatocellular carcinoma(HCC). However, the incidence of distant metastasis was gradually increasing to make the prognosis of patients with HCC worse. Lungs are the most common distant metastatic organs from HCC. Therapy of pulmonary metastasis from HCC was still disappointing with the median overall survival less than 1 year for individual differences in patients and tumor heterogeneity. Currently, there was without standard treatment for pulmonary metastases from HCC, and the patients were treated according to the treatment guidelines of advanced HCC combined with lung cancer. Although studies on invasion and metastasis of HCC emerged in a few decades, the detail pathogenesis of lung metastasis remains unclear. This article will summarize the pathogenesis and therapeutic advances of pulmonary metastasis from HCC and emphasize the importance of intrahepatic lesion control and management of pulmonary metastases.